FORMULAS1 SISTIM PIPA BERPORI BAWAH TANAH DAN PENERAPANNYA - Nasjono, Judi K.; Yuwono, Nur; Triatmadja, Radianta (Civil Engineering Forum Teknik Sipil, 2007)
One advantage of saline water intrusion phenomena is that saline water may be obtained from shallow well close to coastline. The method is friendly to the environment. Shallow well of depth less than 40 times of ground water height measured from seawater level produce a small amount of saline water. Additional saline intrusion discharge may be obtained by installing seaward horizontal perforated pipe at the bottom of well. Research of seepage discharge trough perforated pipe has been done using physical model with tree variation of pipe diameter. Each pipe was varied in length, perforation diameter, and gap of perforation. They were placed at three various depths under sand surface. To simulate the tidal fluctuation there was four variation of water level. Discharge was obtained from all model combination. The result of the research is a formula that was derived from Darcy formula. The formula could be useful to design. It indicates that there are correlation between depth of pipe burial, pipe length, pipe diameter, head, porosity of pipe and discharge